1984
DOI: 10.1002/jez.1402290110
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic demonstration of adrenergic innervation to scale melanophores of a teleost fish, Oryzias latipes

Abstract: The possibility of adrenergic innervation to melanophores in scales of Oryzias latipes was investigated using 3H-norepinephrine ('H-NE) by light microscopic autoradiography. When isolated scales were incubated in 3H-NE, there was observed plexus of varicose fibers labeled with 3H-NE which intimately enclosed the stellate processes and cell bodies of melanophores. These labeled fibers could not be detected in cocaine-treated or denervated scales. Potassium ions caused a considerable reduction in the labeling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…By means of autoradiography using radiolabeled NE, Yamada et al (120) succeeded in visualizing the pattern of adrenergic innervation on melanophores of the medaka O. latipes clearly. They also demonstrated the pattern of innervation to erythrophores of the swordtail, X. helleri (121).…”
Section: Sympathetic Innervationmentioning
confidence: 99%
“…By means of autoradiography using radiolabeled NE, Yamada et al (120) succeeded in visualizing the pattern of adrenergic innervation on melanophores of the medaka O. latipes clearly. They also demonstrated the pattern of innervation to erythrophores of the swordtail, X. helleri (121).…”
Section: Sympathetic Innervationmentioning
confidence: 99%
“…system [Finnin and Reed, 19731, since melanophores are innervated by nerve fibers that take up 3H-norepinephrine [Yamada et al, 1984;Miyata and Yamada, 19851 and subsequently release the labeled transmitter upon stimulation [Kumazawa and Fujii, 19841. Histochemical demonstration of the presence of catecholamines [Falck et al, 19621 in nerve fibers surrounding melanophores [Jacobowitz and Laties, 1968;Fernando, 19891 demonstrates monoaminergic innervation.…”
Section: Introductionmentioning
confidence: 99%
“…Dermal melanophores of teleost fishes receive adrenergic innervation (Falck et al, 1969;Reed and Finnin, 1972;Yamada et al, 1984;also cf. Parker, 1948;Bagnara and Hadley, 1973;Fujii and Oshima, 1986) and both electric currents and potassium ions induce melanosome aggregation within the cells through stimulation of their nervous elements (Fuj ii, 1959;Fuj ii and Novales, 1969;Kinosita and Ueda, 1970;Iga, 1975).…”
Section: Subtypes Of Beta Adrenergic Receptors Mediating Pigment Dispmentioning
confidence: 99%
“…Parker, 1948;Bagnara and Hadley , 1973;Fujii and Oshima, 1986). Previous physiological and histological investigations have suggested that both melanopho r es and leucophores of the medaka receive the same adrenergic lnnervation and that the neurotransmitter released is norepinephrine (Iwata et al, 1981;Iga, 1983;Yamada et al , 1984) . In physiological saline , melanophores usually maintain a fully melanosome-dispersed state and leucophores are in a fully leucosome-aggregated state.…”
mentioning
confidence: 99%